Heinrich Rudolph Hertz e o efeito fotoelétrico - Mangili, Arthur Issa (2011)
This study aimed to analyze the experiments made by Heinrich Rudolph Hertz about the photoelectric effect. To this end, we consulted the work Electric Waves: Being Researches On The Propagation Of Electric Action With Finite Velocity Through Space, mainly the part in which the experiment that refers to the photoelectric effect is described. So we want to understand in which context such effect is discussed, looking for evidence that has arisen its discovery